Characterization of nanocrystalline LiNi1-xCoxVO4 prepared by the polymerized complex method - T. Thongtem (2018)
Nanocrystalline LiNi1-xCoxVO4 (x = 0.00, 0.25, 0.50, 0.75 and 1.00) was prepared from Li2CO3, Ni(NO3)2.6H2O, Co(NO3) 2.6H2O and NH4VO3, using tartaric acid as a complexing agent, followed by 450 °C calcination for 12 h. TGA results show that nanocrystallites started to form at 450-550 °C. Inverse spinel LiNi1-xCoxVO4 was detected using the XRD and SAED methods. The calculated lattice parameter increased upon increasing Co concentration. It was in accordance with the increase in the particle size determined using TEM images. A stretching band of VO4 tetrahedra was detected at 651-820 cm-1 using FTIR. V-O vibrational bands analyzed with a Raman spectrometer were shifted to the lower wavenumbers, due to the increase of Co concentration. The selected elements were also analyzed using EDX and AAS to determine the stoichiometric values (x) of the oxides.